PENGARUH JENIS PELARUT TERHADAP KANDUNGAN TOTAL FLAVONOID DAN AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN MATOA (Pometia pinnata) - Suryani, Nyoman Citra; Permana, Dewa Gde Mayun; Jambe, AA GN Anom (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2016)
This research was conducted to determine effect the kinds of solvent to antioxidant activity and total flavonoid of the extract matoa leaf. The experimental design used in this research was a randomized block design with 5 treatments (water, methanol 95%, ethanol 95%, acetone 90% and isopropanol 96%). The treatment was repeated three times to obtain 15 experimental units. The data were analyzed by randomized block design. If there was a significant effect on the observed parameters, then followed by Duncan multiple range test. The result showed that the treatment significantly effected (P<0.01) on antioxidant activity and total flavonoid. The highest of antioxidant was obtained on acetone that was  27.526  mg/100gram GAEAC and IC 50 of 43,53 ppm. The highest of total flavonoid 1,99 % was obtain on methanol treatment.
Keywords: matoa leaves, extraction, solvent, antioxidant, flavonoid